Worker Cooperatives and their Entrepreneurial Process. Theoretical Foundations and Empirical Evidence from the Worker Cooperatives Established in the Valencian Community, 2008-2014 (Journal of Business, Universidad del Pacífico (Lima, Peru), 2018)
The context of worker cooperatives is significantly different from that of traditional firms, and so the study of entrepreneurship also differs considerably. The analysis of the creation of worker cooperatives requires differentiated approaches, as the more conventional models of entrepreneurship do not prove adequate to this end. We analyze certain determinants of the entrepreneurial process from a sociocultural perspective, which is applicable specifically to this type of firm.Based on the most important proposals of the network, business incubation, role, and marginalization theories from the sociocultural and institutional standpoints, we establish causal links between the determinants of the start-up process and the outcomes expected by cooperative entrepreneurs, in terms of both the performance of the firm itself and the personal outcomes anticipated by these entrepreneurs.From a sample of 103 firms out of a total of 633 cooperatives set up in the Valencian Community (Spain) over the period 2008-2014, and by way of a quantitative methodology drawing on structural equations – and specifically, SmartPLS – we analyze the influence of the determinants on the outcomes of entrepreneurship; in so doing, we aim to establish both the influence or the direct effects on these outcomes and the indirect or mediation effects of the respective outcome variables, as well the possible moderation effects that may be exercised between the independent factors.
Keywords: Cooperative entrepreneurship; worker cooperatives; causal relationships; business performance; incentives; structural equations